A New Method for Estimating the Number of Targets from Radar Returns - Liu-Cai Li; Peng-Fei Luo; Gang Li (2009 2nd International Congress on Image and Signal Processing, 2009)
This paper introduced linear frequency modulation (LFM) waveforms and proposed a new method based on the Wigner transformation and Hough transformation, the new method was used to estimate the number of targets contained in the LFM radar returns. At last we got the simulation result through experiments. The simulation results show that as long as the waveforms meet the certain conditions, the number of targets contained in the LFM radar returns can be estimated exactly by the new method, whose algorithm is simple and easy to implement in works, so it has good technical expansibility, so it could not only be applied to the field of military, but also the field of civil.